2020
DOI: 10.20944/preprints202001.0376.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flexible Players within the Sheaths: The Intrinsically Disordered Proteins of Myelin in Health and Disease

Abstract: Myelin ensheathes selected axonal segments within the nervous system, resulting primarily in nerve impulse acceleration, as well as mechanical and trophic support for neurons. In the central and peripheral nervous systems, various proteins that contribute to the formation and stability of myelin are present, which also harbour pathophysiological roles in myelin disease. Many myelin proteins share common attributes, including small size, high hydrophobicity, multifunctionality, longevity, and intrinsic disorder… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 236 publications
(380 reference statements)
0
12
0
Order By: Relevance
“…The Ig-like domain is structurally very similar to the Ig-like domain in MPZL1, although they share only ~46% sequence identity [ 56 ]. P0ct differs drastically from the Ig-like domain, as it has a compositional bias typical for intrinsically disordered proteins (IDPs) [ 57 ] and is highly positively charged, much like MBP [ 12 , 17 ]. Systematic biophysical characterizations using simplified lipid compositions have been performed on P0ct, which revealed that P0ct alone is an IDP in solution but folds upon irreversible association with negatively charged detergent micelles and lipid vesicles [ 58 , 59 , 60 , 61 ].…”
Section: The Molecular Structure Of P0mentioning
confidence: 99%
See 4 more Smart Citations
“…The Ig-like domain is structurally very similar to the Ig-like domain in MPZL1, although they share only ~46% sequence identity [ 56 ]. P0ct differs drastically from the Ig-like domain, as it has a compositional bias typical for intrinsically disordered proteins (IDPs) [ 57 ] and is highly positively charged, much like MBP [ 12 , 17 ]. Systematic biophysical characterizations using simplified lipid compositions have been performed on P0ct, which revealed that P0ct alone is an IDP in solution but folds upon irreversible association with negatively charged detergent micelles and lipid vesicles [ 58 , 59 , 60 , 61 ].…”
Section: The Molecular Structure Of P0mentioning
confidence: 99%
“…Experimental evidence suggests that P0ct differs from MBP in one noteworthy aspect during membrane association: when MBP binds to a single membrane, a partially folded intermediate state is formed, which can further adhere to a second membrane given that MBP reaches a critical concentration [ 12 , 63 ]. On the other hand, P0ct as a free polypeptide completely embeds into model membranes ( Figure 3 a) [ 44 ]; however, more studies regarding the binding mode are needed.…”
Section: P0 Is the Executive Pns Membrane Stackermentioning
confidence: 99%
See 3 more Smart Citations